Sophocles, seduction and shrivelling: Ichneutai fr. 316 Radt - Thomas, O. (Cambridge University Press, 2015)
Proposes that this fragment, like other fragments of Ichneutai, betrays the influence of the Homeric Hymn to Hermes.